A Novel Method to Quantify Calcium Response Pattern and Oscillation Using Fura2 and Acridine Orange - Mitsuhiro Morita; Jinichi Susuki; Takanori Moto; Chitose Higuchi; Yoshihisa Kudo (Elsevier, 2004)
To study calcium imaging data of cell populations that have various response patterns in peak amplitude and frequency of calcium oscillation in response to stimulation, comprehensive characterization based on statistical analysis of each response is important. In cultures of cells that are flat and in contact with each other, it is difficult to distinguish individual cells in calcium imaging data. We have developed a novel method to determine areas corresponding to individual cells in calcium imaging data. Rat neonatal cerebral astrocytes were filled with the calcium indicator Fura2, stained with acridine orange, and illuminated with UV light. The cell nuclei were clearly visualized. In addition, the images of these nuclei were useful for analyzing concentration-dependent alteration of calcium oscillation of cultured astrocytes in response to glutamate. This novel method may be useful for studying factors affecting calcium response patterns of cultured cell populations, including culture conditions, stimulus paradigms, and synthetic compounds. Keywords:: calcium oscillation, astrocyte, glutamate, Fura2, acridine orange